Three-dimensional fluoroscopic navigation-assisted surgery for tumors in patients with tumor-induced osteomalacia in the bones. Issue 1 (1st January 2017) - Kobayashi, Hiroshi; Akiyama, Toru; Okuma, Tomotake; Shinoda, Yusuke; Oka, Hiroyuki; Ito, Nobuaki; Fukumoto, Seiji; Tanaka, Sakae; Kawano, Hirotaka
Abstract: Purpose: Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome usually caused by phosphaturic mesenchymal tumors. Segmental resection has been recommended for these tumors in the bones because curettage was found to be associated with a high local recurrence rate. Navigation-assisted surgery provides radiological information to guide the surgeon during surgery. No previous study has reported on the efficacy of navigation-assisted surgery for tumors in patients with TIO. Therefore, the present study aimed to evaluate the efficacy of navigation-assisted surgery for tumors in patients with TIO. Methods: The study included seven patients with TIO who were treated between January 2003 and December 2014 at our hospital. All patients underwent surgical treatment with or without the use of a 3-dimensional (3D) fluoroscopy-based navigation system. The laboratory data and oncological outcomes were evaluated. Results: The follow-up period was 8–128 months. The tumors were located at the femur ( n = 4), ischium, spine and ilium ( n = 1). Of the seven patients, five underwent navigation-assisted surgery and two underwent surgery without navigation assistance. In the two patients who underwent surgery without navigation assistance, a complete cure was not obtained and osteomalacia did not resolve. One of these two patients and the other five patients who underwent navigation-assisted surgery, one patient had incomplete resection due to massive invasion of the tumor into the spinal canal, but five patients achieved complete excision and recovered from osteomalacia. Conclusions: Navigation-assisted surgery using a 3D fluoroscopy-based navigation system is effective for tumors in patients with TIO.